Knowledge of Crimean-Congo Hemorrhagic Fever among Nurses at Al-Nasiriyah City Hospitals in Iraq : Pengetahuan tentang Demam Berdarah Krimea-Kongo di antara Perawat di Rumah Sakit Kota Al-Nasiriyah di Irak - Khulood Mohammed Jasim; Ibtisam Khalaf Abd Ali (Academia Open, 2024)
Background: CCHF caused by a tick-borne virus from the Bunyaviridae family, is a severe viral hemorrhagic fever with a mortality rate of 10–40%. Specific Background: Despite their critical role in treating and preventing CCHF, comprehensive research on CCHF transmission and knowledge among healthcare workers, especially nurses in Al-Nasiriyah, Iraq, is lacking. Knowledge Gap: Current literature lacks detailed studies on the awareness and preparedness of nurses regarding CCHF in high-risk areas. Aims: Aims to assess the knowledge of nurses concerning CCHF in Al-Nasiriyah’s educational hospitals and identify gaps in their understanding to improve disease management and prevention strategies. Results: Utilizing a descriptive cross-sectional design, the study surveyed 500 nurses across five teaching hospitals. The average age of participants was 28.83 years, with a predominant proportion holding diplomas and obtaining information primarily from social media. The results revealed that nurses' knowledge about CCHF was suboptimal, with 69.4% of correct answers and a predominance of moderate knowledge levels. Novelty: This research provides novel insights into the knowledge deficits among nurses in an endemic region, highlighting the critical need for targeted educational interventions. Implications: The findings underscore the necessity for comprehensive educational courses on occupational safety and disease prevention tailored to healthcare workers in endemic areas, aiming to enhance their knowledge and preparedness against CCHF. Highlights: Knowledge Gaps: Nurses’ CCHF understanding is inadequate. Educational Need: Targeted training can improve disease management. Information Sources: Social media use highlights need for reliable sources. Keywords: Crimean-Congo hemorrhagic fever, nurses' knowledge, endemic regions, healthcare education, CCHF prevention